2012
DOI: 10.1002/dta.1365
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and co‐existence of active components of ‘legal highs’

Abstract: The results of a study performed on samples of 'legal highs' seized in head shops by law enforcement and health services in Poland between mid-2008 and mid-2011 are presented. In total, 449 preparations which differed in labelling, net masses, forms of distribution, etc., were analyzed. A variety of sophisticated analytical methods, including gas chromatography-mass spectrometry (GC-MS), liquid chromatography-quadropole time-of-flight mass spectrometry (LC-QTOF-MS), high performance liquid chromatography (HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 22 publications
1
84
0
Order By: Relevance
“…Zuba and Byrska [33] analysed 449 seized 'legal high' samples from October 2008 to June 2011 in Poland, and found that most of the pills were mixtures of two or more ingredients, including but not limited to MDPV, BZP and TFMPP. However, mephedrone was often the sole product component.…”
Section: Discussionmentioning
confidence: 99%
“…Zuba and Byrska [33] analysed 449 seized 'legal high' samples from October 2008 to June 2011 in Poland, and found that most of the pills were mixtures of two or more ingredients, including but not limited to MDPV, BZP and TFMPP. However, mephedrone was often the sole product component.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor which can lead to a serious problem is Forensic Toxicol inconsistencies in the qualitative and quantitative compositions of the offered products. This problem was also discussed by the authors for Coco powder samples [24]. The problem can be exemplified by analysis of the contents of products named ''Taifun''.…”
Section: Composition Inconsistencymentioning
confidence: 97%
“…All of these cathinones are characterized by a pyrrolidine ring structure, making them different structurally and possibly also pharmacologically from other synthetic cathinones Simmler et al, 2013). Among the pyrovalerone cathinones, MDPV is currently the most widely detected and used, both in the EU (European Monitoring Center for Drugs and Drug Addiction, 2014b;Helander et al, 2014;Zuba and Byrska, 2013) and US (Leffler et al, 2014;Marinetti and Antonides, 2013;Spiller et al, 2011). In fact, MDPV has become the most frequently detected and used of all cathinones ("bath salts") in some EU countries (Helander et al, 2014;Zuba and Byrska, 2013) and the US (Leffler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among the pyrovalerone cathinones, MDPV is currently the most widely detected and used, both in the EU (European Monitoring Center for Drugs and Drug Addiction, 2014b;Helander et al, 2014;Zuba and Byrska, 2013) and US (Leffler et al, 2014;Marinetti and Antonides, 2013;Spiller et al, 2011). In fact, MDPV has become the most frequently detected and used of all cathinones ("bath salts") in some EU countries (Helander et al, 2014;Zuba and Byrska, 2013) and the US (Leffler et al, 2014). More recently, a second generation of MDPV-like cathinones, including α-PVP, MDPPP, and MDPBP, has been detected and/or used in several EU countries (Eiden et al, 2013;Helander et al, 2014;Westphal et al, 2011;Zuba and Byrska, 2013) and the US (Elliott and Evans, 2014;Smollin et al, 2011;Thornton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation